Factors of garnishing across the border investments - Khawaja Asif Mehmood; Muhammad Zahir Faridi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Foreign Direct Investment is of immense importance for the developing economies of the world in achieving their growth targets. The aim of our study is to find out the factors which are responsible in attracting foreign direct investment. The data, on the variables chosen, is taken from the year 1972-2010. The results show relationship to FDI that justify the economic theories. Because of the stationarity of the data at 1st difference intercept in accordance to Augmented Dickey Fuller ADF test, Johansen Juselius test has been used for getting the desired results. The results show that all the variables except labor force participation have got a positive impact on FDI. There is a need of sincere efforts from the Government side to prepare the domestic soil in such a way that it should be found attractive for the foreign investors.
Keywords: 330; foreign direct investment; GDP; trade openness; interest rate; political stability